2021
DOI: 10.3390/en14217181
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the Transition to Low-Temperature Heat in the UK: A Review

Abstract: To reach net-zero emissions by 2050, buildings in the UK need to replace natural gas boilers with heat pumps and district heating. These technologies are efficient at reduced flow/return temperatures, typically 55/25 °C, while traditional heating systems are designed for 82/71 °C, and an oversized heating system can help this temperature transition. This paper reviews how heating systems have been sized over time in the UK and the degree of oversizing in existing buildings. It also reviews if lessons from othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…It is not clear what the most common temperature control schemes are for stand-alone domestic heat pump systems in northern Europe, and the literature apparently has little to say directly. Informal discussions and in-passing comments suggest that on-off may be common [34] (supported by [6,35]), with weather compensation [26,[36][37][38] relatively common for newer installations, as already happens for combustion boilers. The UK's relevant standards body, MCS, "requires weather compensation to be available on all space heating systems but does not stipulate how this must be set up," [39], and "6.3.9.…”
Section: Heat Pump Experience In Northern Europementioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear what the most common temperature control schemes are for stand-alone domestic heat pump systems in northern Europe, and the literature apparently has little to say directly. Informal discussions and in-passing comments suggest that on-off may be common [34] (supported by [6,35]), with weather compensation [26,[36][37][38] relatively common for newer installations, as already happens for combustion boilers. The UK's relevant standards body, MCS, "requires weather compensation to be available on all space heating systems but does not stipulate how this must be set up," [39], and "6.3.9.…”
Section: Heat Pump Experience In Northern Europementioning
confidence: 99%
“…UK residential heating, responsible for 10 to 20% of the UK's carbon footprint [1], must decarbonise as part of Net Zero goals to tackle climate change. Gas-fired radiator systems in circa 20 million UK dwellings standing now that will still be in use in 2050 are likely to be replaced with heat pump systems [1][2][3][4][5][6][7][8]. Most of those dwellings currently use TRVs (thermostatic radiator valves) to help avoid overheating, improve comfort and save energy, money and thus also carbon emissions, in compliance with building regulation and guidance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reasons for the oversized radiators in existing heating systems. First, advanced computer-aided design methods were not widely available until the late 1980s [13]. Second, the insulation of building envelopes has improved over the years with for example insulation of wall-cavities, floors, roofs and double-glazed windows.…”
Section: Previous Work Low-temperature Heatingmentioning
confidence: 99%
“…For example, the number of heating degree days in the Netherlands has reduced by 20% over the past 5 decades [14]. Finally, design requirements and the assumption of intermittent operation (i.e., night setback) require oversized radiators [13]. The oversizing factor describes the ratio between available and required radiator output power.…”
Section: Previous Work Low-temperature Heatingmentioning
confidence: 99%
“…As an example, estimations forecast-that the coefficient of performance of industrial waste-based heat pumps can rise from 4.2 to 7.1, thanks to a reduction in DH supply/return temperatures from 80 • C/45 • C to 55 • C/25 • C, while the cost of solar thermal technology can be decreased by about 30% [10,11]. In addition, Reguis et al [12] reviewed the DH networks operating temperatures that are commonly adopted in the UK and abroad, also analysing the pros and cons of low-temperature heat, as well as the adaptability of existing buildings to operate with lower temperatures. On the basis of the experience of Sweden and Denmark, they found that limited retrofitting to existing buildings is sufficient to allow the employment of low-temperature heat during the whole year.…”
Section: Introductionmentioning
confidence: 99%